Effect of kinesio taping on improving pain in patients with patellofemoral pain syndrome: a meta-analysis (Principles and Practice of Clinical Research, 2021)
Abstract:Objective: to evaluate randomized controlled trials and perform a meta-analysis to assess the efficacy of kinesio taping in patellofemoral knee pain, in comparison to other treatment modalities.Methods: meta-analysis of randomized controlled trials (RCTs) investigating the effect of Kinesio taping on Patellofemoral pain syndrome (PFPS). Medline and Cochrane library were searched for relevant RCTs from January 2000 to December 2020. Reference lists were manually checked. Published RCTs comparing kinesio taping and other treatment modalities in adolescents and adults with patellofemoral pain syndrome were eligible for the conclusion. The studies were selected, and their quality was assessed by two review authors. Standardized mean difference (SMD) was used to analyze the continuous outcome using a random effect model.Results: the studies combined included 250 subjects. There was no significant difference between the two groups at rest (SMD=0.26, 95%CI (-0.79, 1.3), z=0.48, p=0.63). Subgroup analysis investigating pain while resting, walking, ascending stairs, and descending stairs was conducted and showed pooled inferior effect when compared to non-taping treatment (SMD=0.38, 95%CI (0.12, 0.65), z=2.85, p=0.004).Conclusion: the kinesio taping method does not seem to be effective in reducing knee pain in patients with patellofemoral pain syndrome.Keywords:  kinesio taping, patellofemoral pain syndrome, VAS, meta-analysis